Sobre a gratidão - Maria Adélia Minghelli Pieta; Lia Beatriz de Lucca Freitas (Arquivos Brasileiros de Psicologia, 2009)
In this article, we make a theoretical review of gratitude. We start by presenting its social function in the view of authors from different fields. Gratitude might play an important role in social equilibrium and cohesion. Then, we approach gratitude in Psychology. In this section, we present research results and theorizing about gratitude, stressing the hypothesis that gratitude develops through childhood. We conclude by drawing attention to the necessity of studies about gratitude in children, to better understand this phenomenon and, if possible, stimulate it, given that it contributes to individual wellbeing.